MASA DEPAN PENDIDIKAN: MEMBANGUN LITERASI AI DAN KETERAMPILAN SOSIAL DALAM KURIKULUM - Syarif Hermawan; Tutuk Ningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Artificial intelligence literacy (AI literacy) is defined as the ability of individuals to understand the working principles of AI, how to use it, its impact on life, as well as the skill of operating AI technology responsibly in the context of daily life. AI has great potential to revolutionize education by automating administrative tasks such as assessment and feedback, while supporting curriculum and content development through technologies such as virtual reality and web-based platforms. AI can also aid in the development of students' social skills by providing teachers with a clear picture of which subjects need to be reevaluated. By leveraging AI technology, we can unlock the potential for significant innovation and advancement in the education system. In this future, the use of artificial intelligence will enable a personalized and adaptive approach to learning.